Computed Tomography of the Lung A Pattern Approach - Verschakelen, Johny A. (Diagnostic Imaging, 2018)
Computed Tomography of the Lung: A Pattern Approach aims to enable the reader to recognize and understand the CT signs of lung diseases and diseases with pulmonary involvement as a sound basis for diagnosis. After an introductory chapter, basic anatomy and its relevance to the interpretation of CT appearances is discussed. Advice is then provided on how to approach a CT scan of the lungs, and the different distribution and appearance patterns of disease are described. Subsequent chapters focus on the nature of these patterns, identify which diseases give rise to them, and explain how to differentiate between the diseases. The concluding chapter presents a large number of typical and less typical cases that will help the reader to practice application of the knowledge gained from the earlier chapters. Since the first edition, the book has been adapted and updated, with the inclusion of many new figures and case studies. It will be an invaluable asset both for radiologists and pulmonologists in training and for more experienced specialists wishing to update their knowledge.